Performance Assessment of Slip Mode Frequency Shift (SMS) Islanding Detection Methods - Ramani, Anis Niza; Gan, Chin Kim; Sapar, Ahmad Farid; Shamshiri, Meysam (2013)
The awareness concerning of the grid connected PV has become vital and a major concern, nowadays. Islanding detection is one of the most dominant challenges for distribution generation system connected to the main grid. Commonly, islanding is not preferable power systems, because it poses a safety hazard and may cause damage to power generation and power supply facilities as a result of unsynchronized re-closer. To ensure the safety and reliability, there are various islanding detection methods which have been proposed by researchers recently. One of the available islanding prevention methods is the Slip Mode Frequency Shift (SMS) method which is very common and has numerous advantages over others. This paper investigates the active islanding detection methods and specifically has been focused on SMS islanding method. The results show that SMS method is successfully proven to be feasible and reliable to supply the demand load during an unintentional fault. In addition, this method offer a good protection for those being implemented in Malaysia.